Exploiting nonlocal filters for high-resolution InSAR DEM generation - Sica F.; Martone M.; Pinheiro M.; Cozzolino D.; Prats-Iraola P.; Poggi G. (IGARSS 2018 - 2018 IEEE International Geoscience and Remote Sensing Symposium, 2018)
Nonlocal filters show outstanding performance in the field of interferometric phase restoration by providing strong filtering power together with high spatial features preservation. In this work we focus on the generation of Digital Elevation Models (DEM) from a pair of interferometric SAR images. In the specific, we aim at comparing the performance of state-ofthe- art InSAR filtering approaches on the basis of their noise suppression and detail preservation capabilities. We exploit a dataset of TanDEM-X SAR data relative to the volcanic area of the Kamchatka region (Russia).